A produção acadêmica sobre as relações étnicorraciais no Brasil e no Ceará: a construção do afrodescendente - Mariz, Silviana Fernandes (2012)
This thesis has as main objective the analysis of the process of formation of a new academic niche here identified as "field of afro ancestry" whose expansion has occurred dramatically in Brazilian public universities from the 1980s, and the examination of their close relationship to cultural hegemony exercised by the United States, also identifying their main theoretical and ideological ingredients that support it. To do so, I also reflect on the process of strengthening of social movements, in particular the black movement, which from the 1980s left the purely political sphere and their demands were transformed into academic demands, fostering closer ties with universities; as well as on the process of national formation of the field of afro ancestry, identifying who were its first constructors and ideologues and what were their main demands - always keeping focused on the expression of these claims in academic-scientific terms. Finally, it composed the framework of analysis of this study the identification of the scholars who, in Ceará, exercised leadership role in building the local afro ancestry field in order to identify and analyze the points of similarity and dissimilarity between the afro ancestry field and the previous hegemonic interpretative tradition in Brazil and Ceará until around the 1980s which was marked by defending the ideal of miscegenation. Thus, the thesis is divided into four parts: the first one is devoted to understanding the field of miscegenation, since it is from this that the field of afro ancestry is constituted, and that is when I analyze the major works of Brazilian intellectuals whose works produced from the late 19th century had as its main focus the debate about the miscegenation and the Brazilian hybrid. In the second part, I reflect on the first initiatives produced by Brazilian intellectuals questioning about the field of miscegenation, as was the case with the so-called Project UNESCO. In the third part, I analyze the process of formation of the field of afro ancestry generally in Brazil, both reflecting on the socio-political context of the Brazilian season as identifying who were its first ideologues, that part is still to examine the main conceptual formulations produced by this field. And finally, in the fourth part, I present analytically the process of formation of the field of afro ancestry in Ceará, identifying the Faculty of Education as the main focus of academic research in this field. As principal methodology it was applied the literature review of academic production of the Post-Graduating Program in Education in the Faculty of Education (FACED) at the Federal University of Ceará (UFC), in particular the theses and dissertations produced by the "Sociopoetic, Culture and Race and Ethnic Relations" from the Line Research “Social Movements, Popular Education and School”. In order to reflect about the ideological formation of this field within the Brazilian public university it was fundamental the conceptualization elaborated by Pierre Bourdieu on the scientific field; I appropriated his notion of field to identify the academic production of afro ancestry as a scientific field. Other scholars have helped me to better reflect on the concepts and categories produced in the context of the field of afro ancestry, for example: Paul Gilroy, I benefited from his reflection on the ideological saturation produced around the idea of Africa, African Diaspora and Afro ancestry, and Homi Bhabha, favored me with their formulations on the concepts of hybridity, of in-between place, of ambivalence and of mimicry. Besides them, Thomas Khun and his concept of paradigm allowed me to think more about the field of miscegenation and its particularities.